A highly stable elastic electrode via direct covalent crosslinking for strain sensors. Issue 12 (15th March 2023) - Wang, Linping; Hu, Ben-Lin; Zhang, Fengyuan; Zhang, Yinxia; Li, Junming; Xu, Tianhua; Li, Run-Wei
Abstract : We developed a highly stable elastic electrode via direct covalent crosslinking and applied as a strain sensor for wearable applications. Abstract : Electrodes are essential components in electronic devices. One challenge in developing wearable electronics involves obtaining elastic electrodes with high mechanical and electrical stability. Poor mechanical and electrical stability in stretchable polymer electrodes often stems from instability of the nodes in the polymer network based on poly(3, 4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS), which has typically been used in elastic electrodes. In this study, soft and long chains were covalently crosslinked to the PSS chains directly via esterification between sulfonic acid and epoxy groups, and is used as the first effective example of the direct covalent-crosslinking of PEDOT:PSS to enhance the mechanical and electrical stability of elastic electrodes. By varying the crosslinking temperature and long chain ratio, the optimal PEDOT:PSS films showed a conductivity of 13 100 S m −1 and a stretchability of up to 50%. The R / R 0 values of these films up to 50% strain were lower than 1.5. Elastic capacitive strain sensors using these crosslinked PEDOT:PSS films as electrodes showed a high linearity of up to 50% strain and excellent stability during cyclic testing. Our study provides a valid solution for enhancing the mechanical and electrical stability of elastic electrodes, indicating the potential of stable elastic PEDOT:PSS electrodes in thin film devices for electronic skin applications.